P. 1
Classical Limit

# Classical Limit

|Views: 6|Likes:

Published by: Michael Parrish on May 18, 2011

### Availability:

Read on Scribd mobile: iPhone, iPad and Android.
See more
See less

12/20/2013

pdf

text

original

# The Classical Limit of Quantum Mechanics

If the theory of quantum mechanics is correct, then when quantum mechanics is applied to big things, it must give the results of classical mechanics. Because quantum mechanics emphasizes potential energy V (x), and classical mechanics emphasizes force F , let’s remind ourselves how they’re related. The deﬁnition of potential energy (in one dimension) is
x

V (x) − V (x0 ) = −
x0

F (x ) dx ,

(1)

where F (x) is the force function — i.e., the force that would be exerted on the particle if the particle were at position x. (I’m not saying that the particle is at x, I’m saying that’s what the force would be if the particle were at x.) Taking the derivative of both sides with respect to x (and using the fundamental theorem of calculus on the right) dV (x) = −F (x). (2) dx In the classical limit, the quantal spread in x will be small. We ask how the expected position (the “center of the wavepacket”) moves:
+∞

x =
−∞

xψ ∗ (x, t)ψ(x, t) dx,
+∞

(3) ∂ψ(x, t) dx. ∂t

so

dx = dt

+∞

x
−∞

∂ψ ∗ (x, t) ψ(x, t) dx + ∂t

xψ ∗ (x, t)
−∞

(4)

But the Schr¨dinger equation tells us how wavefunction ψ(x, t) changes with time: o i h ¯ 2 ∂ 2 ψ(x, t) ∂ψ(x, t) =− − + V (x)ψ(x, t) ∂t h ¯ 2m ∂x2 and ∂ψ ∗ (x, t) i h ¯ 2 ∂ 2 ψ ∗ (x, t) =+ − + V (x)ψ ∗ (x, t) . ∂t h ¯ 2m ∂x2 (5)

(6)

(From here on I’m going to write ψ(x, t) as ψ and V (x) as V .) Thus dx dt = − i ¯ h −
−∞ +∞

x −
−∞ +∞

¯ 2 ∂ 2 ψ∗ h + V ψ ∗ ψ dx 2m ∂x2 ¯ 2 ∂2ψ h + V ψ dx 2m ∂x2 x ∂ 2 ψ∗ ψ dx − ∂x2
+∞ −∞ +∞

xψ ∗ − − ¯2 h 2m

(7) xψ ∗ ∂2ψ dx ∂x2 (8) (9)

= −

i ¯ h +

+∞ −∞

−∞

+∞

xV ψ ∗ ψ dx −
−∞ +∞

xψ ∗ V ψ dx
+∞

= i

h ¯ 2m

x
−∞

∂ 2 ψ∗ ψ dx − ∂x2

xψ ∗
−∞

∂2ψ dx ∂x2

1

but it takes us only part way to our goal. . d2 x dt2 = − h ¯ m m +∞ −∞ ∂ψ ∗ ∂ψ dx + ∂t ∂x +∞ ψ∗ −∞ ∂ ∂ψ dx . If we deﬁne ∂ψ f (x) = xψ ∗ and g(x) = (10) ∂x then +∞ +∞ ∂2ψ xψ ∗ 2 dx = f (x)g (x) dx (11) ∂x −∞ −∞ which suggests integration by parts: +∞ −∞ +∞ f (x)g (x) dx = [f (x)g(x)]−∞ − +∞ f (x)g(x) dx. (This isn’t proof that we’ve made no algebra errors.) The upshot is that in typical situations +∞ [f (x)g(x)]−∞ = 0 (13) so +∞ xψ ∗ −∞ ∂2ψ dx = − ∂x2 +∞ −∞ ∂(xψ ∗ ) ∂ψ dx. it contains h right there! Since the classical F = ma involves the second derivative of position ¯ with respect to time. as it must be. Typically the slope ∂ψ/∂x also falls to zero at both inﬁnity and negative inﬁnity. the answer is yes. I’ll just call it the “integration-by-parts trick”. ψ∗ m ∂x −∞ = −i +∞ ψ∗ −∞ ∂ψ dx ∂x (15) Notice that d x /dt is real. so it has to fall to zero at both inﬁnity and negative inﬁnity. Applying this trick to both integrals of equation (9) gives dx dt +∞ +∞ h ¯ ∂(xψ ∗ ) ∂ψ ∂(xψ) ∂ψ ∗ dx − dx 2m −∞ ∂x ∂x ∂x ∂x −∞ +∞ +∞ +∞ h ¯ ∂ψ ∂ψ ∗ ∂ψ ∗ ∂ψ ∗ ∂ψ = −i dx + dx − dx − x ψ x 2m −∞ ∂x ∂x ∂x ∂x ∂x −∞ −∞ +∞ +∞ h ¯ ∂ψ ∗ ∂ψ + dx − dx = −i ψ ψ∗ 2m ∂x ∂x −∞ −∞ +∞ h ¯ ∂ψ = − m dx . . . and in these atypical cases this argument has to be rethought. ∂x ∂x (14) We’ll use this trick several times. . (There are exceptions to these typical behaviors.) All this is ﬁne and good. −∞ (12) Now remember what the wavefunction is normalized. we take one more derivative of x . that would have been proof that we had made algebra errors. This is clearly not a classical equation.Can we say anything about integrals such as the second integral in square brackets above? Surprisingly. such as the Coulomb scattering wave functions. ∂x ∂t (16) 2 . and does so very rapidly — much more rapidly than linearly. but if our expression for d x /dt had been complex.

m (25) 3 . . ∂x ∂t −∞ ∂ψ ∗ ∂x +∞ +∞ −∞ ∂ψ ∗ ∂ψ dx ∂x ∂t (17) (18) − i ¯ 2 ∂2ψ h +Vψ − ¯ h 2m ∂x2 dx (19) ∂ψ ∗ h ¯ 2 ∂2ψ + V ψ dx . ∂x (24) But remember that the force function is F (x) = −∂V /∂x. ∂x2 ∂x (21) Think about this for a minute: if the integral on the left is z. ∂x (20) but let’s apply the integration-by-parts trick to the ﬁrst integral: +∞ −∞ ∂ψ ∗ ∂ 2 ψ dx = − ∂x ∂x2 +∞ −∞ ∂ 2 ψ ∗ ∂ψ dx. ∂x (22) an expression devoid of ¯ s! Apply the integration-by-parts trick to this integral: h ∂ψ ∗ V ψ dx ∂x −∞ +∞ ∂ψ ∗ V ψ dx ∂x −∞ +∞ ∂ψ ∂ψ ∗ V ψ dx + ψ∗ V dx ∂x ∂x −∞ +∞ ∂ψ ∗ 2 e V ψ dx ∂x −∞ +∞ +∞ −∞ ∂(V ψ) dx ∂x −∞ +∞ ∂ψ = − ψ∗ V dx − ∂x −∞ +∞ ∂V = − ψ∗ ψ dx ∂x −∞ +∞ ∂V = − ψ∗ ψ dx ∂x −∞ = − ψ∗ +∞ +∞ +∞ ψ∗ −∞ ∂V ψ dx ∂x (23) Plugging this result back into equation (22) gives d2 x dt2 = − 1 m ψ∗ −∞ ∂V ψ dx. Thus d2 x dt2 = − 2 e m +∞ −∞ ∂ψ ∗ V ψ dx . two of the hs have cancelled out! We’re not home yet because there’s still an h within the ¯ ¯ square brackets. but we’re certainly making progress. − ∂x 2m ∂x2 Look at that. We have that d2 x dt2 = − 2 h ¯2 e − m 2m +∞ −∞ ∂ψ ∗ ∂ 2 ψ dx + ∂x ∂x2 +∞ −∞ ∂ψ ∗ V ψ dx . whence z is pure imaginary or e{z} = 0. so we use the integration-by-parts trick to get rid of it: d2 x dt2 = = Now use Schr¨dinger’s equation: o d2 x dt2 = = 2¯ h m m − 2 e m +∞ −∞ +∞ −∞ − h ¯ m m 2¯ h m m ∂ψ ∗ ∂ψ dx − ∂t ∂x −∞ +∞ ∂ψ ∗ ∂ψ dx . this equation says that z = −z ∗ .The second-order derivative on the right looks particularly grotesque. t)ψ(x. . t) dx = −∞ 1 F (x) . so d2 x 1 = 2 dt m +∞ F (x)ψ ∗ (x.

dt2 (27) 4 .There it is — F (x) = m This result is called Ehrenfest’s theorem. dt2 (26) d2 x . Note that the result is not F( x ) = m d2 x .

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->